Tetrathionate and Elemental Sulfur Shape the Isotope Composition of Sulfate in Acid Mine Drainage - Balci, Nurgul; Brunner, Benjamin; Brunner, Benjamin; Turchyn, Alexandra V. (Frontiers Media SA, 2017)
Sulfur compounds in intermediate valence states, for example elemental sulfur, thiosulfate, and tetrathionate, are important players in the biogeochemical sulfur cycle. However, key understanding about the pathways of oxidation involving mixed-valance state sulfur species is still missing. Here we report the sulfur and oxygen isotope fractionation effects during the oxidation of tetrathionate (S4O62-) and elemental sulfur (S°) to sulfate in bacterial cultures in acidic conditions. Oxidation of tetrathionate by Acidithiobacillus thiooxidans produced thiosulfate, elemental sulfur and sulfate. Up to 34% of the tetrathionate consumed by the bacteria could not be accounted for in sulfate or other intermediate-valence state sulfur species over the experiments. The oxidation of tetrathionate yielded sulfate that was initially enriched in 34S (ε34SSO4-S4O6) by +7.9‰, followed by a decrease to +1.4‰ over the experiment duration, with an average ε34SSO4-S4O6 of +3.5 ± 0.2‰ after a month of incubation. We attribute this significant sulfur isotope fractionation to enzymatic disproportionation reactions occurring during tetrathionate decomposition, and to the incomplete transformation of tetrathionate into sulfate. The oxygen isotope composition of sulfate (δ18OSO4) from the tetrathionate oxidation experiments indicate that 62% of the oxygen in the formed sulfate was derived from water. The remaining 38% of the oxygen was either inherited from the supplied tetrathionate, or supplied from dissolved atmospheric oxygen (O2). During the oxidation of elemental sulfur, the product sulfate became depleted in 34S between -1.8 and 0‰ relative to the elemental sulfur with an average for ε34SSO4-S0 of -0.9 ± 0.2‰ and all the oxygen atoms in the sulfate derived from water with an average normal oxygen isotope fractionation (ε18OSO4-H2O) of -4.4‰. The differences observed in δ18OSO4 and the sulfur isotope composition of sulfate (δ34SSO4), acid production, and mixed valence state sulfur species generated by the oxidation of the two different substrates suggests a metabolic flexibility in response to sulfur substrate availability. Our results demonstrate that microbial processing of mixed-valence-state sulfur species generates a significant sulfur isotope fractionation in acidic environments and oxidation of mixed-valence state sulfur species may produce sulfate with characteristic sulfur and oxygen isotope signatures. Elemental sulfur and tetrathionate are not only intermediate-valence state sulfur compounds that play a central role in sulfur oxidation pathways, but also key factors in shaping these isotope patterns.
Keywords: sulfur isotopes; tetrathionate; oxygen isotopes; intermediate valence state sulfur; Microbiology; QR1-502; microbial oxidation